Political parties' use of electronic newspapers' political discourse during the election campaign in the Kurdistan Region - محمد, آ.د. محمد دلێر ئەمین محمد; عەلی, م.م.عەلی فەرەج عەلی (Sulaimani Journal for Humanities, 2025)
This study aims to understand Accreditation political parties on the political discourse of online newspapers during election campaigns in the Kurdistan Region. This descriptive study utilizes a field survey methodology for a sample of election office officials from political parties in the Kurdistan Region. The study utilizes a scientific interview tool to arrive at scientific findings related to the study's questions. The study reached a number of conclusions, including: Political parties relied on online newspapers to disseminate their discourse based on several criteria, including age, geographic region, and lifestyle of voters. Short video content, graphics, video reports, press conferences, and political discourse were among the most important types of media content that political parties focused on during the election campaign.